ASSESSMENT OF THE CYTOKINE PROFILE OF PATIENTS WITH ALLERGIC DISEASES, COMPLICATED WITH DYSBACTERIOSIS OF THE LARGE INTESTINE - Алірзаєва Ф. В. (World of Medicine and Biology, 2016)
112 patients with allergic diseases have been examined. The patients were divided into 2 groups: I group (main) - 58 (adults - 18, children - 40) patients suffering from allergic diseases and dysbiosis, II group (comparison) - 34 (adults-12, children - 22) patients with allergic disease, without goiter. The increase in the mean level of IL-6 in adult patients with allergies and dysbiosis secondary to 2.9 times and 1.1 times in comparison with control and group II respectively was noted. The content of IL-1 in the blood in adults with allergies and dysbiosis was exceeded one adult from the control group - in 4,1 times and group II - 1.0. The content of TNF-α was lower in children with urticaria. A significant decrease in the concentration of TNF-α in the serum of children with decompensated stage. Therefore, a combined damage of allergic inflammation and dysbiosis was accompanied by more impaired cytokine network in serum.